Dialogic Customer Communication on Instagram: Representing Relationships Building in Slow Bar Coffee Shops - Kussusanti Kussusanti; Gayatri Atmadi; Nurul Robbi Sepang (LONTAR: Jurnal Ilmu Komunikasi, 2026)
This study examines how dialogic customer communication is represented through Instagram content published by slow-bar coffee shops. Using qualitative content analysis, the study analyzes 100 Instagram posts uploaded by two prominent slow-bar coffee shops in Yogyakarta, Indonesia, namely @klinikkopi and @tadasih, between January 1, 2022, and September 30, 2024. The analysis identifies eight elements of dialogic customer communication: openness, empathy, supportiveness, positiveness, equality, trustworthiness, benevolence, and commitment. The findings reveal that commitment, benevolence, and positiveness are the most prominent elements represented in the Instagram narratives. Analysis of netizens’ comments further indicates that audiences positively interpret and appreciate these relational values. The findings suggest that Instagram functions not merely as a promotional platform but as a digital dialogic space through which emotional attachment and long-term customer relationships are cultivated. The study contributes to the development of dialogic customer communication by demonstrating the salience of commitment, benevolence, and positiveness in digital hospitality contexts. Furthermore, the findings suggest that benevolence, which has received limited attention in interpersonal communication literature, may serve as a complementary dimension to DeVito’s interpersonal communication framework. Practically, the study highlights the importance of communicating relational values through digital platforms to strengthen customer relationships and foster loyalty.